Characterizing buried metallic objects in porous media from attenuation fluctuations (2013)
"Study of attenuation characteristics of electromagnetic signals passing through porous media is becoming increasing relevant in providing important insights into the physical properties of the medium and objects that are buried therein. Laboratory experiments have been carried out in this work to determine the relationship between Q-factor of the electromagnetic signal passing through buried metals and the porosity of the surrounding sediments. Sediments were obtained from Erinle River in Ilobu, Southwestern Nigeria and Iron, Silver and Copper plates of similar dimensions were buried inside box-filled sediment in succession. Electromagnetic signal was passed through metal, sediments and sediments with buried metals while lissajous figures generated at different frequencies were analyzed to assess the impacts of buried objects. Results showed that Q-factor decreased as the porosity of riverbed sediments increased. Of the metals buried inside the sediments, Iron had the most attenuation effect while Silver plates had the least, except at frequency 400Hz where Copper had the least and at 600Hz where there were some overlaps between Silver and Copper. Q-factor increased, for all metals and at all signals frequencies, up to a maximum value at the porosity of 0.24 and thereafter decreased. Knowledge of Q- factor from attenuated signals is therefore, a useful way to characterize and identify buried materials "